The position of two recently described endemic taxa in the system of the genus Saussurea (Asteraceae) - Daniil V. Yusupovsky; Elizaveta A. Pyak (Acta Biologica Sibirica, 2024)
Two new species of the genus Saussurea, endemic to the Chuya Steppe, wast intermountain depression in the south-east of the Russian part of the Altai Mountains, have recently been described on a morphological and phylogenetic basis. Saussurea draconis was found to be closely related to S. salsa and S. turgaiensis from S. sect. Laguranthera. Saussurea × magica was found to originate from the hybridisation between S. amara and S. daurica, belonging to S. sect. Theodorea and S. sect. Laguranthera, respectively. The polyphyly of the latter has been repeatedly demonstrated by the results of molecular phylogenetic analyses, and the position of the species of ser. Salsae (to which S. salsa, S. turgaiensis and S. daurica belong) in this section raises, in particular, obvious doubts. This prompted us to undertake an investigation of the aforementioned species, with a view to clarifying their systematic position, based on an analysis of the ITS1-5.8S-ITS2, rsp16-trnQ, ndhF-rpl32, ycf4-cemA regions and a comparative morphological analysis. The results of this investigation led to the conclusion that the position of S. × magica in S. subgen. Theodorea sect. Theodorea is confirmed. Saussurea salsa, S. daurica, S. turgaiensis, S. kaschgarica and S. pseudosalsa, i.e. species of the ser. Salsae, as well as S. draconis, were transferred from S. subgen. Saussurea sect. Laguranthera to S. subgen. Theodorea sect. Theodorea.